Energy efficiency for reducing carbon footprint in historic buildings: comparing case in the UK and Malaysia - Loron, Mehrdad Sahraei; Ismail, Sumarni; Rahimian, Farzad Pour (Universiti Putra Malaysia, 2012)
Climate changes seem to be one of the controversial conflicts for people in today’s world and reducing carbon dioxide emissions, which are one of the main reasons for climate changes, will be an appropriate solution for this alien. Buildings are one of the main resources for producing carbon dioxide emissions. For instance, around 40 percent of all carbon dioxide emission in the UK comes from buildings and so buildings especially heritage buildings need to improve their performance to contribute carbon reduction. The main aim of this research is to identify some acceptable and convenient ways for reducing carbon dioxide emissions in heritage buildings for controlling climate changes to some extent. In this paper, a desktop study was conducted to review the techniques and technologies to help us for reducing carbon dioxide emissions in heritage buildings. In this paper, the importance of heritage buildings and their elements such as wall, roof, window, door, floor has discussed and the main reasons for increasing energy consumption and carbon dioxide emissions have mentioned. In continuing, principles, risks, materials, methods, techniques and technologies for controlling energy loss of historic building elements have expressed. The results indicate that manufactured and transport of building materials will produce a large amount of carbon emissions and so the continued use of historic and heritage buildings can be an accommodative solution for this issue. For instance, in England in 2000 these processes accounted for more than 10 percent of the UK carbon dioxide emissions. It proves that conservation of heritage buildings is important not only for significant value of these buildings, but also for reduction of carbon dioxide emissions. All the methods, techniques and technologies which have discussed in this paper are correspondent solution for the goal of reduction carbon dioxide emissions that produce through the life-cycle of historic buildings.